2013
DOI: 10.1002/cbm.1892
|View full text |Cite
|
Sign up to set email alerts
|

Community DSPD pilot services in South London: Rates of reconviction and impact of supported housing on reducing recidivism

Abstract: Although findings appear promising, this was a naturalistic study. The sample size was small, but represented all men accepted into the two pilot services. Further evaluation of the role of supported housing and perhaps other details of community supervision should follow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…A group of personality disordered men received into a community DSPD programme were followed up in a study in which some were allocated to supported housing [48]. This allocation was not randomised but based on certain criteria such as motivation or inability to live independently, and is subject to confounding.…”
Section: Resultsmentioning
confidence: 99%
“…A group of personality disordered men received into a community DSPD programme were followed up in a study in which some were allocated to supported housing [48]. This allocation was not randomised but based on certain criteria such as motivation or inability to live independently, and is subject to confounding.…”
Section: Resultsmentioning
confidence: 99%
“…Additional evidence shows that obtaining stable and quality housing is vital to desistance (Bruce, Crowley, Jeffcote, & Coulston, 2014; Metraux & Culhane, 2004). U.K.-based research shows that access to housing support significantly reduces recidivism among male ex-offenders with personality disorders: At 12-month follow-up, 5% of those who received assistance recidivated compared with the 51% predicted without assistance (Bruce et al, 2014), but it is unclear what role public housing assistance plays in an American context and what role collateral sanctions that prevent drug and sex offenders from receiving assistance specifically has on recidivism. Some insight can be gained from looking at results from evaluations of prisoner reentry programs, including positive outcomes when housing is provided as part of aftercare (see B.…”
Section: Resultsmentioning
confidence: 99%
“…Reconviction rates were reduced by 62% among 7,800 prolific and high‐risk offenders who had been in the national Priority Offender Programme, providing intensive community supervision and support (Home Office, ). In a naturalistic study of a separate intensive forensic community treatment service, we demonstrated a 91% reduction in reoffending by high‐risk men with personality disorder (Bruce et al, ). All publically funded services, whether provided by the National Health Service (NHS) or the criminal justice system, are under increasing pressure to demonstrate cost‐effectiveness as well as improve outcomes for offenders.…”
Section: Introductionmentioning
confidence: 88%